Mutation spectrum and clinical investigation of achromatopsia patients with mutations in the GNAT2 gene. Issue 8 (6th May 2019) - Felden, Julia; Baumann, Britta; Ali, Manir; Audo, Isabelle; Ayuso, Carmen; Bocquet, Beatrice; Casteels, Ingele; Garcia‐Sandoval, Blanca; Jacobson, Samuel G.; Jurklies, Bernhard; Kellner, Ulrich; Kessel, Line; et al.
Abstract: Achromatopsia (ACHM) is a hereditary cone photoreceptor disorder characterized by the inability to discriminate colors, nystagmus, photophobia, and low‐visual acuity. Six genes have been associated with this rare autosomal recessively inherited disease, including the GNAT2 gene encoding the catalytic α‐subunit of the G‐protein transducin which is expressed in the cone photoreceptor outer segment. Out of a cohort of 1, 116 independent families diagnosed with a primary clinical diagnosis of ACHM, we identified 23 patients with ACHM from 19 independent families with likely causative mutations in GNAT2, representing 1.7% of our large ACHM cohort. In total 22 different potentially disease‐causing variants, of which 12 are novel, were identified. The mutation spectrum also includes a novel copy number variation, a heterozygous duplication of exon 4, of which the breakpoint matches exactly that of the previously reported exon 4 deletion. Two patients carry just a single heterozygous variant. In addition to our previous study on GNAT2 ‐ACHM, we also present detailed clinical data of these patients.